مصادر الإجهاد المهني لدى أعوان تدخل الحماية المدنية - بلهي حسينة (University of Eloued جامعة الوادي, 2023)
Abstract :This study aimed to reveal the sources of occupational stress among the intervention agents in the secondary unit of civil protection ,El Hadjar Annaba, we have adopted the descriptive approach as the most appropriate to the nature of our study , and to collect data , we built a questionnaire containing 23 items which was applied to a sample of 37 individuals , which were selected using the comprehensive survey method . As for the statistical treatment , it was done using the spss program. The study concluded that the most important sources of occupational stress are ; Professional growth, The relationship with superiors, The workload and The nature of work. ملخص: هدفت هذه الدراسة إلى الكشف عن مصادر الإجهاد المهني لدى أعوان التدخل بالوحدة الثانوية للحماية المدنية -الحجار- عنابة-، واعتمدنا على المنهج الوصفي باعتباره الأنسب لطبيعة دراستنا الاستكشافية، ولجمع البيانات قمنا ببناء استبيان يضم (23) بنداً، طبق على عينة قدرها (37) مفردة باستخدام أسلوب الحصر الشامل لكل وحدات مجتمع الدراسة، وتمت المعالجة الإحصائية للبيانات المجمعة باستخدام برنامج الحزم الإحصائيةspss ، وقد توصلت الدراسة إلى النتائج التالية: أهم المصادر التي تسبب الإجهاد المهني لعينة الدراسة هي ( النمو المهني، العلاقة مع الرؤساء، عبء العمل، طبيعة العمل) .
" دراسة ميدانية بالوحدة الثانوية للحماية المدنية الحجار -عنابة- "
Keywords: مصادر إجهاد مهني; أعوان تدخل; حماية مدنية; Sources of occupational stress; Intervention agents; Civil protection